Patient‐initiated follow up affects fear of recurrence and healthcare use: a randomised trial in early‐stage endometrial cancer. (6th August 2018) - Jeppesen, MM; Jensen, PT; Hansen, DG; Christensen, RD; Mogensen, O
Abstract : Objective: To test the hypothesis that patient‐initiated follow up reduces the fear of cancer recurrence (FCR) and healthcare use when compared with traditional hospital‐based follow up. Design: Pragmatic, multicentre randomised trial. Setting: Four Danish departments of gynaecology between May 2013 and May 2016. Population: One hundred and fifty‐six women diagnosed with International Federation of Gynecology and Obstetrics (FIGO) stage I low‐intermediate risk endometrial carcinoma. Methods: Women allocated to the control group attended hospital‐based follow up consisting of regular outpatient visits for 3 years after primary treatment. Women in the intervention group were instructed in patient‐initiated follow up, which included careful instruction in alarm symptoms and options for self‐referral rather than a schedule of examinations. Main outcome measures: The primary end point was FCR as measured by the Fear of Cancer Recurrence Inventory (FCRI) after 10 months of follow up. Secondary end points included cancer‐related use of primary and secondary health care during the first 10 months after treatment. Results: In the primary analysis, FCR decreased significantly more in the control group from baseline to 10 months of follow up (difference −5.9, 95% CI −10.9 to −0.9). The majority of this improvement happened after only 3 months of follow up. Women receiving the intervention had fewer examinations at the department compared with the control group (0 versus 2 median visits, P < 0.01) and 58% of these examinations were scheduled because of vaginal bleeding. Conclusions: Hospital‐based follow up alleviates FCR significantly more than patient‐initiated follow up, though the estimated difference was small. Patient‐initiated follow up is a feasible, potentially cost‐reducing follow‐up approach in a population of endometrial cancer survivors with low risk of recurrence. The decision to use patient‐initiated follow up should balance these benefits and harms. Tweetable abstract: Patient‐initiated follow up reduces healthcare use but maintains fear of recurrence in endometrial cancer. Plain Language Summary: Why and how was the study carried out?: Follow up of women with endometrial cancer is resource consuming and previous research suggests that it is not effective. Even though the women benefit from reassurance at follow up, routine examinations may also remind the women of the disease and induce fear of cancer recurrence. Furthermore, routine follow up may delay recurrence diagnosis, because the women do not report their symptoms until the next scheduled visit. In the research explained in this article, patient‐initiated follow up was evaluated as an alternative to traditional follow up. The women were randomly assigned to one of two follow‐up programmes: regular gynaecological examinations at the department of gynaecology or self‐referral with careful instruction in alarm symptoms, that is, patient‐initiated follow up. The level of fear of cancer recurrence in the two groups was obtained by questionnaires. Information on healthcare use was obtained by questionnaires and a chart review. What were the main findings?: Regular examinations at the department of gynaecology reduced the fear of cancer recurrence significantly more than patient‐initiated follow up, though the difference was small. Women who were instructed in alarm symptoms, under self‐referral, were able to monitor their symptoms, and this approach significantly reduced the number of examinations at the department of gynaecology. What are the limitations of the work?: Participants in the self‐referral group knew that they were examined less than other women, and this may have induced fear of cancer recurrence. Similarly, the regular completion of questionnaires regarding fear of cancer recurrence may have reminded the women of the disease and diminished the difference between the two groups. What are the implications for patients: Patient‐initiated follow up reduced healthcare use but maintained fear of cancer recurrence in women who had survived early‐stage endometrial cancer. Future analyses on quality of life and cost‐effectiveness are needed to balance the benefits and harms of patient‐initiated follow up. Tweetable abstract: Patient‐initiated follow up reduces healthcare use but maintains fear of recurrence in endometrial cancer.